Step (1): Assume given statement
Let the given statement be P(n), i.e,
P(n):11⋅2⋅3+12⋅3⋅4+13⋅4⋅5+⋯+1n(n+1)(n+2)
=n(n+3)4(n+1)(n+2)
Step (2): Checking statement P(n) for n=1
Put n=1 in P(n), we get
P(1):11⋅2⋅3=1(1+3)4(1+1)(1+2)
⇒16=44⋅2⋅3
⇒16=16
Thus P(n) is true for n=1
Step (3): P(n) for n=K
Put n=K in P(n) and assume this is true for some natural number K i.e,
P(K):11⋅2⋅3+12⋅3⋅4+13⋅4⋅5+⋯+1K(K+1)(K+2)
=K(K+3)4(K+1)(K+2) ⋯(1)
Step (4): Checking P(n) for n=K+1
Now we shall prove that P(K+1) is true whenever P(K) is true.
Now, we have
11⋅2⋅3+12⋅3⋅4+13⋅4⋅5+⋯+1K(K+1)(K+2)+1(K+1)(K+2)(K+3)
=K(K+3)4(K+1)(K+2)+1(K+1)(K+2)(K+3) (using (1))
=1(K+1)(K+2)[K(K+3)4+1(K+3)]
=1(K+1)(K+2)[K(K+3)2+44(K+3)]
=1(K+1)(K+2)[K(K2+6K+9)+44(K+3)]
=1(K+1)(K+2)[K3+6K2+9K+44(K+3)]
We can write it as
=1(K+1)(K+2)[K3+2K2+K+4K2+8K+44(K+3)]
= 1(K+1)(K+2)[K(K2+2K+1)+4(K2+2K+1)4(K+3)]
=1(K+1)(K+2)[(K2+2K+1)(K+4)4(K+3)]
=(K+1)2(K+4)4(K+1)(K+2)(K+3)
=(K+1)(K+4)4(K+2)(K+3)
We can write it as
= (K+1)((K+1)+3)4((K+1)+1)((K+1)+2)
Thus P(K+1) is true whenever P(K) is true.
Final answer:
Therefore, by the principle of mathematical induction statement P(n) is true for all n∈N.